The implementation of non-Voigt line profiles in the HITRAN database: H2 case study. (July 2016) - Wcisło, P.; Gordon, I.E.; Tran, H.; Tan, Y.; Hu, S.-M.; Campargue, A.; Kassi, S.; Romanini, D.; Hill, C.; Kochanov, R.V.; Rothman, L.S.
Abstract: Experimental capabilities of molecular spectroscopy and its applications nowadays require a sub-percent or even sub-per mille accuracy of the representation of the shapes of molecular transitions. This implies the necessity of using more advanced line-shape models which are characterized by many more parameters than a simple Voigt profile. It is a great challenge for modern molecular spectral databases to store and maintain the extended set of line-shape parameters as well as their temperature dependences. It is even more challenging to reliably retrieve these parameters from experimental spectra over a large range of pressures and temperatures. In this paper we address this problem starting from the case of the H2 molecule for which the non-Voigt line-shape effects are exceptionally pronounced. For this purpose we reanalyzed the experimental data reported in the literature. In particular, we performed detailed line-shape analysis of high-quality spectra obtained with cavity-enhanced techniques. We also report the first high-quality cavity-enhanced measurement of the H2 fundamental vibrational mode. We develop a correction to the Hartmann–Tran profile (HTP) which adjusts the HTP to the particular model of the velocity-changing collisions. This allows the measured spectra to be better represented over a wide range of pressures. The problem of storing the HTP parameters in the HITRAN database together with their temperature dependences is also discussed. Abstract : Highlights: The problem of non-Voigt line shape representation in spectroscopic database is addressed. Available experimental data for H2 rovibrational transitions are collected and reanalyzed. An upgrade of the Hartmann–Tran profile is proposed to handle untypical H2 line shapes